In silico prediction of candidate gene targets for the management of African cassava whitefly (Bemisia tabaci, SSA1-SG1), a key vector of viruses causing cassava brown streak disease - Kaweesi,Tadeo; Colvin,John; Campbell,Lahcen; Visendi,Paul; Maslen,Gareth; Alicai,Titus; Seal,Susan (PeerJ, 2024)
Whiteflies (Bemisia tabaci sensu lato) have a wide host range and are globally important agricultural pests. In Sub-Saharan Africa, they vector viruses that cause two ongoing disease epidemics: cassava brown streak disease and cassava mosaic virus disease. These two diseases threaten food security for more than 800 million people in Sub-Saharan Africa. Efforts are ongoing to identify target genes for the development of novel management options against the whitefly populations that vector these devastating viral diseases affecting cassava production in Sub-Saharan Africa. This study aimed to identify genes that mediate osmoregulation and symbiosis functions within cassava whitefly gut and bacteriocytes and evaluate their potential as key gene targets for novel whitefly control strategies. The gene expression profiles of dissected guts, bacteriocytes and whole bodies were compared by RNAseq analysis to identify genes with significantly enriched expression in the gut and bacteriocytes. Phylogenetic analyses identified three candidate osmoregulation gene targets: two α-glucosidases, SUC 1 and SUC 2 with predicted function in sugar transformations that reduce osmotic pressure in the gut; and a water-specific aquaporin (AQP1) mediating water cycling from the distal to the proximal end of the gut. Expression of the genes in the gut was enriched 23.67-, 26.54- and 22.30-fold, respectively. Genome-wide metabolic reconstruction coupled with constraint-based modeling revealed four genes (argH, lysA, BCAT & dapB) within the bacteriocytes as potential targets for the management of cassava whiteflies. These genes were selected based on their role and essentiality within the different essential amino acid biosynthesis pathways. A demonstration of candidate osmoregulation and symbiosis gene targets in other species of the Bemisia tabaci species complex that are orthologs of the empirically validated osmoregulation genes highlights the latter as promising gene targets for the control of cassava whitefly pests by in planta RNA interference.
Keywords: Bemisia tabaci; Gene targets; Osmoregulation; Sucrase; Aquaporin; Alpha-glucosidase; Symbiosis; Portiera aleyrodidarum; RNA intereference; Pest management